2011
DOI: 10.1007/s12199-011-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

Delay in the treatment of pulmonary tuberculosis: a report from Afghanistan

Abstract: Objectives The aim of this study was to determine the length of delays and to investigate the factors associated with patient (care-seeking) and health-system (treatment initiation following care-seeking) delays, among smearpositive tuberculosis patients in Kunar province, Afghanistan, as delay in diagnosis and treatment results in more severe disease, higher mortality, and a longer period of infectivity in the community. Methods A cross-sectional study of 122 new smearpositive pulmonary tuberculosis patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 9 publications
6
30
2
1
Order By: Relevance
“…Similarly, majority of TB patients involved in this study were from the rural parts of south Ethiopia. In line with the findings of the present study, inquiries made by researchers in Afghanistan [8], Nigeria [13] and Indonesia [16] had found being resident in the rural area as risk factor for delayed initiation of treatment. The main reasons for this unacceptably longer duration before treatment might be due to geographical access to health service and cost of transportation to reach to the health facility in a longer distance from their residence [12].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly, majority of TB patients involved in this study were from the rural parts of south Ethiopia. In line with the findings of the present study, inquiries made by researchers in Afghanistan [8], Nigeria [13] and Indonesia [16] had found being resident in the rural area as risk factor for delayed initiation of treatment. The main reasons for this unacceptably longer duration before treatment might be due to geographical access to health service and cost of transportation to reach to the health facility in a longer distance from their residence [12].…”
Section: Discussionsupporting
confidence: 91%
“…The median delay was lower than the estimate in India [9], Afghanistan [8], Kathmandu in Nepal [14], Brazil [10], Indonesia [16] and West Midland in England [17]. This difference emanates from only new smear positive pulmonary TB patients in Nepal, Brazil and Afghanistan partly.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The diagnostic delays observed in the studied patients are lower than those reported from EMR and countries of origin of the patients [7][8][9][10][11][12][13]. A systematic review of the Indian literature found that the patient, diagnostic and treatment delay were 18.4, 31.0 and 2.5 days, respectively, and the median total delay of 55.3 days [14].…”
Section: Discussionmentioning
confidence: 63%